Formation of V. Vernadsky's noospheric ideas as the basis of the educational pedagogical policy strategy - Samodryn, A.; Moskalyk, H.; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Khavina, I.; Leushyna, O. (My University, 2021)
The aim of the scientific research is a philosophical comprehension of the noosphere ideas of Academician V.I. Vernadsky under the prism of temporal and socio-political changes. Spirituality is considered as an educational goal of the human true. The study focuses on the analysis and design of future humanity - a biosphere cell-the region's noosphere and its unit matrix - a noosphere-educated integral personality. The authors of the study intend to carry out a philosophical analysis of the world life under the conditions of civilizational changes and transformations.The theoretical research is based on the works of V.I. Vernadsky and his followers: Whitehead A., Fedorov N., Schelling F.I.J., Spengler O., Samodrin A. and others. The application of methods that helped to conduct theoretical research-analysis and synthesis, systematization of materials, historical and logical, comparative, systemic and structural, allowed to study the essence of the research problem. Our study is an attempt through the prism of V.I. Vernadsky's personality to notice the guidelines for improving the noosphere personal potential formation mechanisms of the Ukrainian for the success of effective shifts of education and science in the direction of noosphere consciousness revolution.
Keywords: biosphere; culture; education; human; noosphere; pedagogical policy